The Effect of Naupli Artemia Feeding Which is Enriched by Squalene In Different Dose on The Growth and Survival Rate of Juvenile Sea Horse - Limin Santoso (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
A feeding experiment was conducted to determine the optimal dose of growth and survival rate for sea horse(Hippocampus kuda) juveniles (initial average weight 0.074 g, initial average body length 18 mm and old 16 days). Completely randomized design with five treatments and three replications were use: A (naupli artemia), B (naupli artemia + squalene 0,3 g/L), C (naupli artemia + squalene 0,6 g/L), D (naupli artemia + squalene 0,9 g/L), E (naupli artemia + squalene 1,2 g/L). The results showed that the growth and survival rate of the juvenile sea horse content increased. There was significant differences (P<0.01) in  survival  rate  (SR),  growth  of  body  weight  (AW),  and  growth  of  body  length  (AL).  Based  on  the evaluation of the some parameters; SR (69, 97%), AW (0,320 g) and AL (2,67cm), SGR (5, 43%/day). It can be concluded that treatment D (naupli artemia + squalene 0,9 g/L) is optimal for growth and survival rate for sea horse juveniles.   Key words : sea horse juvenile, different dose, enriched by squalene